Association Between Health-Related Quality of Life and Motor Function in Ambulant and Nonambulant Duchenne Muscular Dystrophy Patients. (December 2019) - Gocheva, Vanya; Schmidt, Simone; Orsini, Anna-Lena; Hafner, Patricia; Schaedelin, Sabine; Rueedi, Nicole; Weber, Peter; Fischer, Dirk
This cross-sectional study assessed health-related quality of life (HRQOL) in ambulant and nonambulant patients with Duchenne muscular dystrophy, and explored the association between health-related quality of life and clinically assessed motor function. The Pediatric Quality of Life Inventory (PedsQL) Generic Core Scale and PedsQL Neuromuscular module were completed by 34 parent-child dyads. Association between PedsQL scores and overall motor abilities and the transfers and standing posture domain measured by the Motor Function Measure were examined. Child self-reported and parent proxy-reported mean PedsQL scores for children with Duchenne muscular dystrophy were lower than those for healthy children for the physical and psychosocial health-related quality of life. Fifty-six percent of patients reported clinically impaired psychosocial health-related quality of life scores. Several aspects of the generic and disease-specific health-related quality of life in patients with Duchenne muscular dystrophy were positively associated to overall motor function and transfers and standing posture domain. Associations remained stable when adjusted for age and corticosteroid use. The Motor Function Measure is clinically meaningful in the context of a patient's day-to-day life.